Guttaflow bioseal versus monocone obturation technique. A scanning electron microscopy study - Mustaffa, Musliana; Nordin, Nuradlin; Embong, Siti Nur Hanie; Mahdan, Mohd Haidil Akmal; Kharuddin, Azrul Fazwan; Mohd Ibrahim, Mohamad Shafiq (2019)
Background The understanding on how well GuttaFlow Bioseal (GFB) conforms to the root canal irregularities is unclear and requires further investigation.